NORMATIVE HEAT-TRANSFER COEFFICIENT OF THE RESIDENTIAL BUILDING - A. E. Piir; O. A. Kozak; I. M. Agafonov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The paper offers a simple but sufficiently accurate technique of the mid-normative heattransfer coefficient for any dwelling house applying the known dimensions, required thermalprotection level and specified facade-glazing portion. The authors present the ascertainment technique of the mid-normative heat-transfer coefficient for a dwelling house with the number of stories from 1 to 16 and the required level of thermal protection. They establish the theoretical dependence and parameters affecting the rate of heat-losses through the external building borders. The article considers the thermal-protection level effect on the heating load and the heating-season fuel consumption rate and finds the correlation between the regulatory requirements to the thermal resistance of certain elements of the building.The authors note the effect of the building geometrical characteristics on the heat-losses rate of the wall portion in the total area of the external borders and its relative quantity as compared with the floor-space of the heated accommodations. The comparison of the specific heat-losses computation results for buildings of 1-, 2-, 4-, 8and 16-storeys with the SNiP 23-02–2003 maximum permissible values show the computational results being less than the maximum values on average by 12 %. This permits recommending the normative heat-transfer coefficient of dwelling houses for evaluating heat-loses at the concept-design stage with the building external-borders engineering constructions being indeterminate or yet under development.